Preparing for the future : strategic planning in the U.S. Air Force - Barzelay, Michael; Campbell, Colin, 1943- (Washington, D.C. : Brookings Institution Press, 2003)
Annotation "This study provides an inside look at how the Air Force came to formulate and declare its "strategic intent" for developing the organization's capabilities over a timeline of more than twenty years. Air Force strategic intent is not a plan, but a shared commitment to strengthening specific core competencies and critical future capabilities. Michael Barzelay and Colin Campbell reveal how one of the nation's most significant public organizations has reassessed its own strategic intent." "Drawing lessons from the Air Force experience, this book provides a significant contribution to public management research on innovation and executive leadership. One key lesson is that preparing for the future is a responsibility that organizations can discharge effectively if they combine insights with practical knowledge of executive leadership and the dynamics of policy change. Preparing for the Future provides a fresh argument about innovation and leadership in public management, while breaking new ground in the analysis of management practices, such as strategic visioning."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.
Methodological Appendix -- Index.
Includes bibliographical references (pages 241-256) and index.
Print version record.
English.
JSTOR
Keywords: United States. -- Air Force -- Reorganization; États-Unis. -- Air Force -- Réorganisation.; United States. -- Air Force; United States. -- Air Force -- Reorganization; Military planning -- United States; Strategic planning -- United States; Planification militaire -- États-Unis.; Planification stratégique -- États-Unis.; TECHNOLOGY & ENGINEERING -- Military Science; POLITICAL SCIENCE / Public Affairs & Administration; Armed Forces -- Reorganization; Military planning; Strategic planning; United States; Strategic planning -- United States; Military planning -- United States